Comparative Influence of Imidafenacin and Oxybutynin on Voiding Function in Rats with Functional Urethral Obstruction - Fukata, A.; Yamazaki, T. (Drug Research, 2016)
An antimuscarinic therapy may increase the risk of voiding dysfunction. However, it is unclear whether the relative risk of voiding dysfunction is different among antimuscarinics. Therefore we determined the potencies both in enhancing the bladder capacity (BC), effectiveness, and in decreasing the maximum urinary flow rate (Qmax), voiding dysfunction, to compare their therapeutic indices.Under urethane anesthesia, urinary flow rate was measured at distal urethra using an ultrasonic flow meter in female Sprague-Dawley rats with functional urethral obstruction induced by a continuous i. v. infusion of α1-adrenoceptor agonist A-61603 (0.03 μg/kg/min). In a separate group of urethane-anesthetized rats without urethral obstruction, an intermittent cystometry was performed to determine BC.Intravenous imidafenacin and oxybutynin produced a significant dose-dependent decrease in Qmax with the minimum doses of 0.03 and 1 mg/kg, respectively. Imidafenacin and oxybutynin markedly increased BC, with minimum doses of 0.01 and 3 mg/kg, respectively. At the minimum dose to increase BC, oxybutynin caused a significant increase in residual urine volume with a significant decrease in voiding efficiency, whereas imidafenacin had no influence on these values. The relative influence index, which is the ratio of the minimum influence dose between in decreasing of Qmax and in increasing of BC, of imidafenacin was 10 fold higher than that of oxybutynin.This study suggests that imidafenacin has a lower relative risk of voiding difficulty compared with oxybutynin in rats. These results provide new information that antimuscarinics may have varying degrees of impact on voiding difficulty.
Keywords: overactive bladder; benign prostatic hyperplasia; imidafenacin; oxybutynin; urinary flow